PROBLEMS AND SOLUTIONS IN THE SYSTEM OF TRAINING OF QUALIFIED PERSONNEL IN UZBEKISTAN ON THE BASIS OF INTERNATIONAL STANDARDS - Esanov Muzaffar Xoshimovich (Scholar Express Journal, 2021)
The implementation by the Republic of Uzbekistan of treaties and conventions in the field of human rights, education, children's rights, taking into account the world's best practices in the field of training is one of the factors in its development. The state policy in the field of training envisages the formation of a comprehensively developed citizen through a system of continuous education, which is inextricably linked with the intellectual and spiritual-moral upbringing of a person. In this way, one of the most basic constitutional rights of a citizen is the right to education, creative ability, intellectual development, and the right to work in the profession. However, obvious problems in the educational process need to be addressed. This article discusses the problems in the system of training qualified personnel in Uzbekistan in accordance with international standards and their solutions
Keywords: Qualified personnel; problems in the education system; system reform; international standards